2022
DOI: 10.1007/s00467-022-05785-x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal growth restriction followed by very preterm birth is associated with smaller kidneys but preserved kidney function in adolescence

Abstract: Background Preterm birth and fetal growth restriction (FGR) are associated with structural and functional kidney changes, increasing long-term risk for chronic kidney disease and hypertension. However, recent studies in preterm children are conflicting, indicating structural changes but normal kidney function. This study therefore assessed kidney structure and function in a cohort of adolescents born very preterm with and without verified FGR. Methods Adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…A recently published study has explored the correlation between FGR, including SGA cases and preterm birth, and kidney size and kidney function by measuring several biochemical markers, such as the renin-angiotensin-aldosterone system (RAAS), in adolescents. Although the researchers observed that FGR and preterm birth were associated with smaller total kidney volume, no statistical difference in the biochemical markers of kidney function or RAAS components, including angiotensinogen, was found in this study, which is in accordance with our own angiotensinogen findings [46]. Moreover, these findings were consistent with the previous results of research into fetal growthrestricted sheep wherein the researchers reported significant reductions in the sheep's kidney weight but no evidence of alteration in the renal RAS components [47].…”
Section: Discussionsupporting
confidence: 91%
“…A recently published study has explored the correlation between FGR, including SGA cases and preterm birth, and kidney size and kidney function by measuring several biochemical markers, such as the renin-angiotensin-aldosterone system (RAAS), in adolescents. Although the researchers observed that FGR and preterm birth were associated with smaller total kidney volume, no statistical difference in the biochemical markers of kidney function or RAAS components, including angiotensinogen, was found in this study, which is in accordance with our own angiotensinogen findings [46]. Moreover, these findings were consistent with the previous results of research into fetal growthrestricted sheep wherein the researchers reported significant reductions in the sheep's kidney weight but no evidence of alteration in the renal RAS components [47].…”
Section: Discussionsupporting
confidence: 91%
“…The abnormal growth and development of these organs from FGR are what lead to childhood and adulthood morbidities that increase risks associated diseases such as fatty liver disease, obesity, and cardiovascular disease 6,7,32 . Studies identifying the precise malperfusions and functional consequences have been and continue to be investigated for these various organ systems [48][49][50][51][52][53] . We are the first to show a treatment correcting fetal growth and one of the most prominent and significantly disordered features of FGR.…”
Section: Discussionmentioning
confidence: 99%
“…Early onset FGR (<32 weeks gestation) and severe FGR (<3 rd percentile) are associated with up to 1.5-fold increased risk of stillbirth and a 2 to 5-fold risk of perinatal death (9). Long term complications of FGR include increased childhood morbidity, and even cardiovascular, metabolic, and neuropsychiatric diseases in adulthood (2,4,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Non-malarial etiologies of FGR include maternal comorbidities, placental dysfunction, genetics, and environmental exposures (e.g.…”
Section: Introductionmentioning
confidence: 99%